Relapse causes in alcohol dependence: a cross-sectional study - Kalyoncu, Ayhan; Mırsal, Hasan; Pektaş, Özkan; Yazıcı, Ali Hilmi; Mırsal, Nursel; Beyazyürek, Mansur (Journal of Dependence, 2001)
Object: There is a close relation between sobriety and causes of relapses. Negative emotional states, social pressure and interpersonal conflict are frequent causes of relapse in alcohol dependence. The aim of this study is to investigate the relapse causes by examining the main risk factors. Method: The participants were 24 patients who were hospi- tilizated in our clinic between September 1998 and March 1999 after a relapse. One of the including criteria is to have received a structured treatment program in the past. The patients were evaluated by using a sociodemographic data form, a semi-structured interview form for clinical features, consumption types and high risk situations, Hamilton Depression Scale, SCL 90 R. SPSS packed program was used to evaluate the data . Results: Four female (16.7%)and twenty male (83.3%) patients included to the study. The average age of subjects were 39.8 (ss=5.8).The average time periond after the last inpatient treatment was 5.7 (sd=3.6) month and the average time spent until the following re-treatment after the first alcohol intake was 31.4 (sd=59.7) clay . The rate of relapse factors were 33.3% (n=8) for negative feelings, thoughts, and behaviours, 20.8% (n=5) for problems with treatment, 16.7% (n=4) and social pressure, 16.7% (n=4) for interpersonal conflicts, 12.5% (n=3) for drives, craving, missing and trying for controlled consumption. Discussion: In this study, it seemed that negative feelings, thoughts, attitudes and behaviours have been found to be important relapse causes in alcohol dependence following the first six-month period after treatment. A different finding from other studies, we observed that difficulties during the process of receiving regular outpatient treatment constituted the important part of the problem.